(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
A typical consequence of head trauma and a notable finding during such autopsies is subdural hematoma (SDH). Upon diagnosis, a variety of clinical manifestations, including the lethal acute SDH, subacute, or chronic SDH (CSDH), may be present. Sometimes, these traumas may be so trivial that the exact history of incidence may be difficult to elicit, especially in the cases of subacute and chronic SDH. The signs of subacute SDH are usually evident only after three days to 2 to 3 weeks and grossly appear during autopsy as dark red-black liquefied blood with blood clots. CSDH is a gelatinous membrane with outer and inner layers adherent to dura matter. The present case is of a 47-year-old man with histories of falls, at his residence, first two years no history of treatment was there and a recent fall, about two weeks and led to the initial presentation of hemiparesis and hospitalization with a diagnosis of SDH, the patient died after a week. This article discusses the findings observed in the case where the cause of death was due to the complication of SDH, which was found to be subacute on the chronic type. Such cases usually present late to the hospital due to delayed symptom onset, and high suspicion of such cases should be kept when patients have a history of minor trauma or bleeding disorders and especially when the patient is elderly. Such cases necessitate immediate diagnosis via imaging modalities of the intracranial hemorrhages and necessary intervention.